Factores explicativos del funcionamiento en memoria en pacientes con síndrome de fibromialgia - Becerra-García, Juan Antonio (International Journal of Psychology and Psychological Therapy, 2018)
﻿The aim of this study was to contribute to the knowledge of the variables that may be associated with memory performance in a group of patients with fibromyalgia (FM). The study examines the relationship among memory performance and socio-demographic, psychological and somatic variables; it also attempts to estimate the explanatory power of the studied variables in memory performance. A total of 20 participants diagnosed with FM completed various measures of memory performance (immediate recall, delayed recall, recognition and working memory), and different psychological (attentional span, anxious-depressive symptoms and personality) and somatic measures (somatic symptoms and pain intensity). Significant correlations were found among memory performance capacities and the different types of variables evaluated. The subsequent regression analysis showed that only the variables years of study, pain intensity and attentional span were independently associated with immediate recall, recognition memory and working memory. These findings suggest that in this sample the examined psychosocial and somatic variables are associated differentially with different memory capacities. This study contributes to learning more about variables associated with memory performance on FM.
Explanatory factors in memory performance in patients with fibromyalgia syndrome
Keywords: fibromyalgia; memory; education; pain; attention; Scopus